1999
DOI: 10.3348/jkrs.1999.40.5.965
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcoma after Preoperative Chemotherapy: Tissue Characterization with Specimen MR and the Role of Enhanced MR Imaging

Abstract: Preoperative intra-arterial chemotherapy and limbsalvage surgery for the treatment of osteosarcoma has led to marked improvement in long-term patient survival (1 3). The most accurate prognostic factor is the percentage of tumor necrosis after chemotherapy (4). Purpose : To evaluate the role of enhanced MR imaging in monitoring tumor response to preoperative chemotherapy for osteosarcomas. Materials and Methods : Fo r t y -s even patients (30 males and 17 females, with a mean age 17 years ; range 8 44 years) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…These findings are supported by other studies which also failed to find a significant correlation. [ 13 24 25 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are supported by other studies which also failed to find a significant correlation. [ 13 24 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…Though few studies have reported its significant role in predicting histological response, many studies have given an equivocal report. [ 13 24 ] Although increase in tumor volume correlates well with the poor histological response, reduced or stable tumor volume does not guarantee a good response. [ 14 25 26 ]…”
Section: Introductionmentioning
confidence: 99%